Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1093/clinids/14.4.841
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Due to Rhodotorula Related to Use of Indwelling Central Venous Catheters

Abstract: With increased use of surgically implanted silastic central venous catheters, there has been an increase in the recovery from blood cultures at Memorial Sloan-Kettering Cancer Center (New York) of environmental and skin organisms including the red yeast Rhodotorula. From 1985 through 1989, 23 patients had catheter-related Rhodotorula sepsis. All 23 patients had indwelling central venous catheters that had been in place from 1 to 22 months (average, 9.3 months) prior to the detection of fungemia. All patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
84
0
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 7 publications
6
84
0
9
Order By: Relevance
“…1 In rare instances, Rhodotorula species have been reported to cause septicemia, 2 meningitis, 3 systemic infection, 4 and sepsis related to complications from indwelling central venous catheters. 5 Rhodotorula species have a rapid growth rate on culture and mature in four days. The colony is usually pink to coral, but can also be orange-red to yellow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In rare instances, Rhodotorula species have been reported to cause septicemia, 2 meningitis, 3 systemic infection, 4 and sepsis related to complications from indwelling central venous catheters. 5 Rhodotorula species have a rapid growth rate on culture and mature in four days. The colony is usually pink to coral, but can also be orange-red to yellow.…”
Section: Discussionmentioning
confidence: 99%
“…The case was successfully treated with miconazole and 5-flucytosine. 7 In 1992, Kiehn et al 5 reported 23 patients who had catheter-related Rhodotorula sepsis within five years at Sloan Kettering Cancer Center (New York). All 23 patients had indwelling central venous catheters that had been in place from one to 22 months (average 9.3 months).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to C. albicans, Rhodotorula sp. has been implicated as the etiologic agent of central venous catheter infection and fungemia [5][6][7][8][9] . In recent years, there has been an increasing search for new antifungal compounds due to the lack of efficacy, side effects and or resistance associated with some of the existing drugs [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…to antifungal and antiseptic agents [25,26] . This study was aimed to confirm the usage of Algeria honey as antifungal and antiseptic agents and evaluate this inhibitory action at different honey concentration against C. albicans and Rhodototorula sp.…”
Section: Introductionmentioning
confidence: 99%
“…Immunocompromised patients, particularly those with central venous catheters or other indwelling devices, are at highest risk for infection (10,14,18). While Rhodotorula strains appear to be less virulent than the more common yeast pathogens such as Candida and Cryptococcus neoformans, Rhodotorula infection has been associated with a crude mortality of up to 15% (12) and can cause sepsis syndrome and other life-threatening complications (4,10,13). Rhodotorula bloodstream infections have been successfully managed with line removal alone, antifungal therapy without line removal, and with a combination of these approaches (7,10).…”
mentioning
confidence: 99%